Ethnopharmacological survey of medicinal plants used in the traditional treatment of kidney stones realized in Fez-Morocco - Ammor, Kenza; Mahjoubi, Fatima; Bousta, Dalila; Chaqroune, Abdellah (Ethnobotany Research and Applications, 2020)
Background: This survey was carried out in the prefecture of Fez-Morocco in order to establish an inventory of medicinal plants used in the treatment of urolithiasis pathology and to collect as much information as possible about the therapeutic uses and recipes reported by the local population. Methods: An ethnobotanical survey undertaken between January 2015 to December 2017 in the region of Fez-Meknes (Morocco) which includes the urban community of Fes-Medina, Hassan II University Hospital Center, and Sidi Hrazem which include the thermal Spring. A total of 380 individual who knew about and/or had used the medicinal plants for the indicated disease, including some herbal healers. The inventory of medicinal plants is summarized in a synoptic table, which contains the scientific, vernacular and common name of the plant, the part of the plant used, and the preparation mode is presented. The data were analysed through relative frequency of citations (RFC). Results: After the analysis of the data collected, 54 plant species belonging to 28 families, including that of the Apiaceae (19 %), the most represented with 9 species. Similarly, the results obtained show that the majority of the medicinal plants used in the treatment of lithiasis are prepared as decoction from aerial parts. Among the most cited plants we find Herniaria hirsuta L., Zea mays L., Opuntia ficus indica L., Zizyphus lotus L, Ammi visnaga L. and Petroselinum sativum Hoffm. Conclusion: This study showed the importance of herbal remedies for the treatment of kidney stones. The understanding use of these medicinal plants for the treatment of renal lithiasis can contribute to the identification of natural active molecules which can be useful in pharmacology. Keywords: Kidney stones, Ethnobotanical survey, Medicinal plants, Therapeutic uses, Fez-Meknes (Morocco).